Eosinophilic Granuloma Complex (EGC) In Persian Crossbreed Cat: A Case Report - Putry, Adisty Gelsa; Noviatri, Aldila; Rickyawan, Nofan; Setiyowati, Rini; Kristanto, Dwi (Jurnal Veteriner, 2026)
Inflammatory lesions that often occur in the oral cavity of cats include Eosinophilic Granuloma Complex (EGC). The aim of this research is to reveal the impact of surgical procedures followed by antibiotic and anti-inflammatory therapy on the incidence of EGC.  A 3-year-old 2.2 kg persian mix cat had clinical symptoms of irregular mass growth of the lips under the tongue beginning 2 months prior and had difficulty eating. According to the owner, the cat was the result of inbreeding/incest Clinical examination revealed pink oral mucosa, mass on the back, abdomen and legs, the cat's mouth cannot close because of an irregular mass (2.5 × 2.5 × 2.5 cm) of pale yellowish pink colour in the lingual frenulum, pink nodules on the lower lip and pink plaque under the chin. The results of the blood test revealed a predominance of eosinophils and neutrophils. Postoperative histopathological examination of the granuloma mass revealed the presence of reactive fibroblasts, irregular collagen fibres, and a predominance of eosinophils, stem neutrophils and lymphocytes. Treatment of eosinophilic granuloma complex (EGC) can be performed by surgical excision of granuloma masses via electrocautery, and drug therapy including amoxicillin and potassium clavulenate (20 mg/kg BW), meloxicam (0.05 mg/kg BW), and multivitamins (1 ml/day) can be continued. Fourteen days of postoperative therapy resulted in rapid and effective wound healing. The conclusion of this study shows that the combination of surgical procedures and medications such as antibiotics, non-steroidal anti-inflammatory drugs and vitamins has a positive impact on the treatment of EGC cases.